Feminism in dance an overview and in the works of Denis Reyes - Jacinto, Joelle Florence Patricia B. (Diliman, Quezon City University of the Philippines, 1999)
This paper seeks to find the connection between dance and female empowerment, and whether it can apply in the Philippines.This thesis will often look at Western ideologies, feminist perspectives, as well as cultural and artistic values, while hardly touching on those non-western countries neighboring the Philippines.
Keywords: Dance